(untitled) (Communications in Computational Physics, 2018)
We study the spin-dependent electron transport by using ab initio calculations for a molecular junction consisting of a phenylene capped by two carbon chains which is sandwiched between two zigzag-edged graphene nanoribbon (ZGNR) electrodes modulated by external magnetic fields or ferromagnets. It is shown that the spin-charge transport can be adjusted by the phenylene rotation angles in respect to ZGNR electrodes and spin orientation in electrodes. Specifically, we demonstrate that the proposed molecular device exhibits switching, (dual) spin-filtering, rectifying, negative differential resistance (NDR) effects. Interestingly, when the phenylene rotation angle is θ=60◦, the maximum value of the peak-to-valley ratio of NDR is up to 26, the spin-resolved rectification ratio can reach up to 2.47×104, and the spin filtering efficiency reaches up to 100%. The physical mechanisms of these effects are analyzed via the spin-resolved transmission spectrum associated with local density of states (LDOS) and molecular projected self-consistent Hamiltonian (MPSH) eigenvalues.